Strategies, Challenges and Solutions for Intensive Reading: The Case of Science Undergraduate Students at the University of Botswana - Pitse; Balibi (American Journal of Education and Practice, 2024)
Purpose: Reading is a vital communication skill that every university student should be proficient in. The demands for reading at university are very high and continue to grow as students move further into high levels of study in their different disciplines. Students are expected to intensively read a wide variety of material such as prescribed texts, journal articles, newspapers, magazines and lecture slides. Intensive reading goes beyond simply understanding facts to also requiring skills that enable a student to critically analyze, synthesize, evaluate, and review information. The need for reading comprehension skills that enable the reader to concentrate for lengthy periods and yet recall and retrieve information is critical. Students need to develop more active reading strategies that enable them to read independently and effectively hence, a student that fails to develop effective reading skills faces difficulties in constructing accurate comprehension of content. This study explores strategies that students possess for intensive reading. It also investigates the challenges that students encounter while reading intensively and proposes solutions to these challenges. Materials and Methods: Three theories of reading; namely, the schema theory, the Conscious Raising (CR) approach and social constructivist theory, formed the theoretical framework for the study. Data were collected using a questionnaire administered on 180 first year science students at the University of Botswana registered for the Communication and Academic Literacy course during the first semester of the 2019/2020 academic year. Data were analyzed quantitatively using frequency counts and simple percentages. Findings: Analysis of data revealed that science students encounter numerous challenges associated with intensive reading. Furthermore, the majority of them lack knowledge of effective reading strategies which will help them navigate through the myriads of reading assignments that they are expected to undertake during the course of their study. Implications to Theory, Practice and Policy: A number of useful solutions have been adduced to assist students deal with the challenges associated with intensive reading.